2019
DOI: 10.2224/sbp.7805
|View full text |Cite
|
Sign up to set email alerts
|

Ability emotional intelligence and life satisfaction: Humor style as a mediator

Abstract: We examined the path effect of humor style (HS) in terms of ability emotional intelligence (EI) and life satisfaction (LS) with 260 Chinese university students. The ability EI, HS, and LS of participants were measured with Chinese language versions of the measures, including the Emotional Intelligence Scale, the Humor Styles Questionnaire, and the Life Satisfaction Scale. We found that EI and LS were positively correlated. Positive HS (affiliative and self-enhancing) positively mediated EI and LS, and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
3
5
0
2
Order By: Relevance
“…A sufficiently high level of emotional intelligence helps to trigger and manage the necessary external emotions (Clark, 2016). Also, emotional intelligence helps maintain positive emotions and evokes a subjective sense of life satisfaction (Huang & Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A sufficiently high level of emotional intelligence helps to trigger and manage the necessary external emotions (Clark, 2016). Also, emotional intelligence helps maintain positive emotions and evokes a subjective sense of life satisfaction (Huang & Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, humour is a multidimensional trait referring to a group of specific stimuli that can lead to fun. After perceiving stimulation from humour, individuals will generate cognitive or emotional experiences and responses that can be explicitly observed (Huang & Lee 2019). Empirical research (Abel 2002;Kuiper, McKenzie & Belanger 1995) has shown that greater use of humour is associated with appraising events in a more positive, less threatening manner.…”
Section: Spoofing Destination Marketing For Political Sarcasmmentioning
confidence: 99%
“…Higher life satisfaction and positive affect correlated with higher EI ( Cazan and Nastasa 2015 ; Extremera and Rey 2016 ). Huang and Lee ( 2019 ) reported EI positively related to affiliative and self-enhancing humor, while it negatively associated with aggressive and self-defeating humor.…”
Section: Introductionmentioning
confidence: 99%